The Duration of Pauses between Phrases in Reading Language - Kazlauskienė, Asta; Kalašinskaitė, Eidmantė (Respectus Philologicus, 2020)
The aim of this research is to determine the duration of the pauses between paragraphs and sentences in reading language and their connection with the length and reading speed of said language units. The research material consists of 48 sound recordings (eight Lithuanian speakers read six texts representing different functional styles). The results show that all readers usually pause between paragraphs and the duration of those pauses depend on the reading speed: faster readers pause for approximately 400–1340 ms, while slower readers pause for 750–1800 ms. Pauses are the shortest after short paragraphs and they are 1.2 times longer after longer paragraphs. All the readers usually pause between sentences as well. Faster readers on average pause for 200–980 ms, slower readers pause for 340–1360 ms. The longer the sentence, the longer the pause after that sentence (up to 1.4 times). However, the pause can be the same duration after both long and medium length sentences.
Keywords: pause; sentence; paragraph; duration